Vaccine co-administration in paediatric age: the experience of theLocal Health Unit of Cuneo-1 (Ambito di Cuneo), Italy - Pellegrino, A.; Busellu, G.; Cucchi et al., A. (Acta Biomedica Atenei Parmensis, 2011)
Background and aim of the work: The immunization schedule might be continuously updated on the basis of the new scientific and epidemiological knowledge, possible changes in operational requirements and the availability of new products. A high vaccination compliance is strictly related to factors such as tolerability, effectiveness and number of injections. This last has always been a critical point and combined vaccines guarantee high levels of safety and immunogenicity requiring fewer injections and accesses to services. Co-administration should be considered in order to expand the supply of important vaccinations, (eg. meningococcal and pneumococcal), avoiding the increase of the number of accesses to services. Methods: Since January 2007, an experience with the co-administration of hexavalent vaccine together with conjugate pneumococcal and meningococcal C vaccines started at the LHU CN1-Ambito di Cuneo. The target of this co-administration, based on scientific criteria, is to provide immunization against St. pneumoniae and N. meningitidis in newborns. Results: Considering that the coverage rate (VC%) with hexavalent vaccine has been always high and that, at the end of 2006, the VC% for the pneumococcal and meningococcal C conjugate vaccines were equal to 50.4% and 44.4%, in this first year of experience the compliance to co-administration has significantly increased from 47% of doses administered in the first quarter of 2007 to 65% in the first quarter of 2008. Conclusions: Co-administration could be an useful mean to introduce new immunizations into the vaccination schedule and to achieve high vaccination coverage rates.